Remittances and Life Cycle Deficits in Latin America - Ricardo Bebczuk; Diego Battistón (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2010)
The paper investigates the effect of remittances on the coverage of financial deficits arising during youth and retirement years and their influence on some household behaviors. To this end, household survey information is used from Ecuador, Honduras, Mexico and Nicaragua to perform a number of econometric tests exploring the linkage between remittances and a battery of health, education and work outcomes dealing with young and elderly household members. The main overall finding is that, with variations across countries and regression specifications, remittances generally appear to exert a positive and robust impact. In particular, with few exceptions, remittances (a) respond to the lack of pensions and especially to overall household financial deficits; (b) encourage co-residence of the elderly with younger relatives; (c) facilitate elderly's retirement; (d) increase household expenditures in health and education; (e) foster public and private school attendance, inhibits child labor, and improve anthropometric measures.
Keywords: 330; Latin America; remittances; life cycle; retirement; Rücküberweisungen; Lebenseinkommen; Lateinamerika